In-service and Pre-service Teachers’ Orientations to Linguistic, Cultural and Worldview Diversity - Anuleena Kimanen; Jenni Alisaari; Arto Kallioniemi (Uludag University, Faculty of Education, 2022)
Culturally and linguistically responsive education takes the learners’ diverse identities and languages into account in many ways. This article explores the orientations that emerge when pre-service and in-service teachers evaluate their preparedness to conduct certain culturally and linguistically responsive practices. Exploratory factor analysis was conducted on survey data from 181 respondents. In general, teachers’ orientations towards culturally and linguistically responsive pedagogy were positive. Three orientations were identified: orientation to culture, to language and learning, and to affirming identities, with the last being the strongest. Gender, training on multicultural education and current professional status had a significant influence on respondents’ orientations. The results give valuable information for developing teacher education to better respond to the needs of those teaching diverse learners.